Abnormal Poisson's ratio and linear compressibility in perovskite materials - Huang, C. W. (2013)
The Poisson's ratio of perovskites with a high degree of anisotropy can change from negative to positive and become much larger than the normally observed range of 0.2–0.4 and even greater than the isotropic upper limit 0.5 along certain crystallographic orientations. These results pave the way for a better understanding of elastic-mediated physical properties of perovskites by engineering the orientation-dependent Poisson's ratios.